Reading Profiles in Adolescents with Fragile X Syndrome and Down Syndrome - Puente, Anibal; Alvarado, Jesús M.; Jiménez, Virginia; Martínez, Lourdes (Anales de Psicología / Annals of Psychology, 2017)
Fragile X Syndrome (FXS) and Down Syndrome (DS) read better than expected for their mental age. We have measured three basic reading skills (word recognition, phonological awareness, and reading comprehension), and two standard intellectual and verbal measures: the McCarthy Scales of Children’s Abilities and Peabody Picture Vocabulary Tests. The tests were applied to 16 adolescents classified as FXS (M = 14.74 years old, SD = 4.03) and 16 adolescents classified as DS (M = 15.59 years old, SD = 2.35). For comparison purposes, the reading tests were also applied to a typical develop group of 70 children aged between 4.8 and 7.0 years (M = 6.11, SD = 0.71). Children with DS and FXS exhibited verbal skills superior to their cognitive development, especially in the FXS group. In reading performance, FXS showed a reading level corresponding to 5/6 their age, and for SD 6/7 of the equivalent reading age, however, both groups exhibited a similar reading performance in the three reading skills measured, when nonverbal mental age was controlled.